Impact of Regulation on Economic Behavior: Discussion - Bower, R. S. (Journal of Finance, 1981)
R. S. Bower, Impact of Regulation on Economic Behavior: Discussion, The Journal of Finance, Vol. 36, No. 2, Papers and Proceedings of the Thirty Ninth Annual Meeting American Finance Association, Denver, September 5-7, 1980 (May, 1981), pp. 397-399